HTTP blocking in MM: facebook.com, instagram.com, signal.org, telegram.org, twitter.com +2 more (Myanmar) - Voidly (2026)
WARNING severity censorship detected in Myanmar. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0006
Keywords: censorship; MM; censorship; warning